FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN IBU BERSALIN TERHADAP PERTOLONGAN PERSALINAN OLEH BIDAN DI PUSKESMAS PONED UJUNGJAYA TAHUN 2013 - Nurasih Nurasih; Endang Nurrochmi; Atin Ukayah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
Issues on maternal and perinatal health in Indonesia still become a national problem that needs to get top priority. Efforts to reduce maternal mortality rate (MMR) should be focused on the direct cause; one of the ways to prevent it is to do births attended by skilled health personnel in health facilities, including in this case the provision of PONED (basic emergency obstetric neonatal care) health centers. The level of patient satisfaction is influenced by midwives’ attitude, communication, and work experience in attendance at the birth. The objective of this study was to determine the factors that affect the level of maternal satisfaction during childbirth attended by a midwife at Ujungjaya PONED Health Center of Sumedang District in 2013. This was an analytic research using a cross sectional approach. The population was mothers who underwent childbirth in the study site in the period of January-December 2013 amounted to 38 persons. The sample was taken using non-random sampling. Data analysis in this study used univariate and bivariate analysis with the Chi Square. The results of univariate analysis showed the majority of respondents said that the midwives had a positive attitude, could perform good communication, and had work experience of more than 10 years. The results of the bivariate analysis showed that there was an influence of midwives’ attitudes toward maternal satisfaction with a P Value of 0.006. Midwives’ communication and work experience also influenced the level of maternal satisfaction with a P Value of 0.004 and 0.016, respectively. This shows the influence of attitude, communication and work experience of midwives in attendance at the birth to the level of maternal satisfaction at Ujungjaya PONED Health Center of Sumedang in 2013. The health center is therefore advised to improve services and the midwives are expected to perform self-evaluation, correction and introspective to improve services